Use of physical education means in younger school-aged pupils after acute seasonal viral infections of the upper respiratory tract - Radziejowska, Maria (Journal of Education, Health and Sport, 2018)
The purpose of this scientific work is to define the dependency level of knowledge in the period of health promotion, the peculiarities of life style, pupils’ state of health at the age of 7 – 9 after recovering from respiratory diseases against the background of seasonal viral infections of upper respiratory tracts. The parents’ opinions, some indicators of the state of the circulatory system and the respiratory system and the medical documentation of 553 pupils from different Kyiv secondary schools (Obolon district) were analyzed and 538 pupils in cities of Szczecin (West Pomerania province) and Konin (Wielkopolska province). The dependence‘s assessment of some indicators of the respiratory system and elements of children’s life style at the age of 7 – 9, using the Spearman’s rank correlation coefficient (the confidence level p <0,05000, n = 1091), showed that a strong direct dependence exists only between the using of hardening procedures and the size of the chest circumference. Researches show that there is the necessity of a new understanding of the situation and the development of effective approaches for increasing physical activity, maintaining and strengthening the somatic children’s health recovered from respiratory diseases. Also, we need to solve the problem of training of professionals who will implement it.